The effects of dextrin concentration as filler on physical, chemical, and microbiology properties of powdered goat milk kefir - Rizqiati, H.; Nurwantoro, N.; Susanti, S.; Prayoga, M. I. Y. (Diponegoro University, 2021)
The purpose of the research was to study the effects of dextrin powder with a different concentration on the physical, chemical, and microbiology properties of the product. The research was conducted using a Completely Randomized Design (CRD) with five treatments and four replications, namely the addition of dextrin filler with a concentration of 0% (T0), 2,5% (T1), 5% (T2), 7,5% (T3), and 10% (T4) (w/v). The quality of powdered goat milk kefir that is analyzed are physical, chemical, and microbiology properties. The data were analyzed using SPSS 26.0 application using Analysis of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT). The test results show a significant difference in dextrin concentration (P<0.05) on solubility, total acid content, yield, water content, protein content, pH, total dissolved solids, carbohydrate, lactic acid bacteria, yeast, and microbe content of the product and shows no significant difference on the viscosity of the product. It can be concluded that the addition of dextrin can increase the yield, solubility, total dissolved solids, water content, carbohydrate, total microbe, lactic acid bacteria, and microbe but also decreased the pH value and the protein content, with the best treatment was the addition of dextrin of 10%.